Eksistensi Madrasah Diniyah Takmiliyah Management dan Keberadaannya di Tengah Penguatan Sistem Pendidikan: Penelitian - Habibissajidin, Habibissajidin; Mawardi, Mawardi; Kompri, Kompri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study discusses the existence of Madrasah Diniyah Takmiliyah, which is still widely found in various regions. Madrasah Diniyah Takmiliyah plays an important role in educating the community—especially the younger generation—by instilling moral and religious values from an early age. This role becomes even more crucial amid the rapid flow of information and technological advancement, where the boundaries of space and time have virtually disappeared due to the extensive use of online (digital) data technology in daily life. Discussing an educational institution known as a madrasah will always be interesting and seemingly inexhaustible, particularly when viewed from the aspect of its management. Management is essential for any institution—whether consciously realized or not—as a fundamental prerequisite for achieving institutional goals. The better the management applied, the greater the likelihood that the institution will succeed in reaching its objectives, and vice versa. In reality, many Islamic educational institutions, particularly madrasahs, still exhibit levels of productivity that fall short of expectations. Therefore, this paper provides an overview of madrasah management, the problems faced within it, possible solutions, and formulations for further development of these institutions.